2021
DOI: 10.3390/cancers13092280
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles and Their Current Role in Cancer Immunotherapy

Abstract: Extracellular vesicles (EVs) are natural particles formed by the lipid bilayer and released from almost all cell types to the extracellular environment both under physiological conditions and in presence of a disease. EVs are involved in many biological processes including intercellular communication, acting as natural carriers in the transfer of various biomolecules such as DNA, various RNA types, proteins and different phospholipids. Thanks to their transfer and targeting abilities, they can be employed in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 129 publications
(176 reference statements)
0
19
0
Order By: Relevance
“…Currently, researchers are focusing on utilizing exosomes produced by cancer cells as cancer vaccines and utilizing exosomes derived from microorganisms, as well as engineered cells, as vaccines to protect the host against infectious diseases [ 99 , 100 , 101 ]. The EV-based vaccine against cancer has garnered the most attention for preventing tumor development or treating existing tumors [ 102 ]. Compared with conventional vaccines, EV-based vaccines offer unique traits valuable in vaccine design, such as better biosafety and efficiency as antigen-presenting systems and adjuvants [ 103 ].…”
Section: Therapeutic Value Of Extracellular Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, researchers are focusing on utilizing exosomes produced by cancer cells as cancer vaccines and utilizing exosomes derived from microorganisms, as well as engineered cells, as vaccines to protect the host against infectious diseases [ 99 , 100 , 101 ]. The EV-based vaccine against cancer has garnered the most attention for preventing tumor development or treating existing tumors [ 102 ]. Compared with conventional vaccines, EV-based vaccines offer unique traits valuable in vaccine design, such as better biosafety and efficiency as antigen-presenting systems and adjuvants [ 103 ].…”
Section: Therapeutic Value Of Extracellular Vesiclesmentioning
confidence: 99%
“…Currently, researchers are focusing on utilizing exosomes produced by cancer cells as cancer vaccines and utilizing exosomes derived from microorganisms, as well as engineered cells, as vaccines to protect the host against infectious diseases [99][100][101]. The EV-based vaccine against cancer has garnered the most attention for preventing tumor development or treating existing tumors [102].…”
Section: Therapeutic Value Of Extracellular Vesiclesmentioning
confidence: 99%
“…Other common associated markers include LOX [173][174][175], MMP [173][174][175], Twist [176,177], STAT3/IL-6 [178][179][180][181][182][183], MAPK/ERK [184][185][186], Sox-2 [187][188][189][190], Oct-4 [191][192][193], and c-Myc [194][195][196][197]. While the HIF family remains the primary mediators of the hypoxic response, research also points towards exosomal involvement in various hypoxic functionalities [151,[198][199][200][201]. Given their vesicular nature, exosomes' involvement in the TME does shine light on the possibility of their usage as next-gen NCs, specifically in the context of CSC-targeting.…”
Section: Stem Cell Involvement In Tumor Microenvironment Regulationmentioning
confidence: 99%
“…The application of both natural and bioengineered EVs, as well as artificial EV-like nanoparticles for therapeutic delivery systems, has been a topic of growing interest due to their nano-scale size, natural origin and ability to encapsulate various biomolecules within the lipid bilayer membrane. EVs, including certain TEVs, have been proposed to serve as a cancer vaccine given that they naturally carry antigenic peptides capable of eliciting antitumor immune responses [ 19 , 20 ], yet this idea has not been tested in BC. In this current study, we applied a preclinical MB49 syngeneic mouse model and found that BC-derived EVs are immunoactive and can prevent autologous tumor growth through a mechanism primarily mediated by CD8 + T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%